PENGARUH ATRIBUT PRODUK WISATA DAN ELECTRONIC WORD OF MOUTH (E-WOM) TERHADAP KEPUTUSAN BERKUNJUNG DALAM PERSPEKTIF BISNIS ISLAM PADA OBJEK WISATA BUKIT ASLAN (STUDI PADA PENGUNJUNG BUKIT ASLAN DI BANDAR LAMPUNG) - Rezeki Kurniawati; Fatih Fuadi; Suhendar Suhendar (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to analyze the influence of Tourism Product Attributes and Electronic Word of Mouth (E-WOM) on Visiting Decisions from an Islamic Business perspective at the Bukit Aslan tourist destination in Bandar Lampung. The main issue explored is how these two factors affect tourist behavior in making visiting decisions. A quantitative approach was used with a survey method involving 92 respondents selected through purposive sampling. Data were analyzed using SmartPLS 4 software. The results show that both Tourism Product Attributes and E-WOM have a partial and simultaneous significant effect on Visiting Decisions. Tourism Product Attributes obtained a T-Statistic value of 2.427 (P-Value 0.016), while E-WOM scored a T-Statistic of 4.705 (P-Value 0.000), with an R² value of 0.606. This means both variables explain 60.6% of the variation in visitor decisions. These findings support the Theory of Planned Behavior (TPB), especially in the components of attitude and subjective norms that shape intention and action. The implication of this study highlights the importance of managing quality tourism products and implementing effective digital communication strategies to enhance the appeal of local tourism destinations.